The Visual Brain, Perception, and Depiction of Animals in Rock Art. (22nd July 2013) - Hodgson, Derek
Abstract : Several aspects of the depiction of animals in rock art can be explained by certain perceptual correlates relating to the visual brain and evolutionary factors. Recent evidence from neuroscience and the visual brain not only corroborates this claim but provides important new findings that can help delineate which graphic features relate to biological/genetic criteria. In addition to highlighting how the insights from visual science and evolutionary studies can promote a greater understanding of the depictive strategies employed to portray animals, this paper will also explore ways in which the findings from these disciplines can be assimilated with semiotics that provide novel insights into the preference for depicting animals in a particular format over an extended period. The emphasis throughout is placed on dual-inheritance theory where culture and evolutionary determinants are seen as complementary.